Green Banking Performance in Indonesian and Malaysian Islamic Banks: A Maqasid Shariah Framework - Salsabila, Fairuz Fasyah; Fitriyah, Fitriyah (LPPM ISNJ Bengkalis, 2026)
Purpose – The purpose of this study is to analyze the performance of green banking in Islamic banking in Indonesia and Malaysia based on the maqasid shariah framework. Method – This study is a quantitative study. The sampling technique used is purposive sampling, resulting in a sample size of 21 banks, comprising 11 Indonesian Islamic banks and 10 Malaysian Islamic banks. The data source used is secondary data in the form of annual financial reports of Islamic banks from 2022 to 2024. The data analysis technique uses the Maqashid Syariah Index approach and the Simple Additive Weighting method. The difference in performance between the two countries is tested with an independent sample T-Test using SPSS analysis tools. Findings – The results of this study indicate that there is a significant difference between the green banking performance of Islamic banks in Indonesia and Malaysia based on the maqasid shariah index. Implications – This study can provide insights and contribute to the literature on green finance performance based on the maqasid sharia framework, particularly in the banking sector in Indonesia and Malaysia. This study can serve as a guide for Islamic banks in Indonesia and Malaysia to understand the extent to which green banking performance contributes to achieving sustainability and social welfare goals and provide recommendations for improving green finance.